TechSync - Ruba Qawareeq; Islam Atallah (My University, 2025)
In the rapidly evolving world of technology, it’s important for students to stay informed and. connected with their peers, especially computer engineering students. With the university courses that need cooperation and participation most of time, there was a need for a platform to achieve this. So, TechSync is a platform that came to help computer engineering students on their learning journey. This platform enables students to access their courses materials, quizzes, and make a discussion with other members about the course. Also, user can come to offer a paid/ free course on related fields. And there is a code editor to enable students to test their code online, and collaborate with other colleagues. In this platform user can create a project and add its tasks then can divide the tasks between team members which make it easy for the team to collaborate and work together. Also, users can share their experience, tips, with other users to help them growth. And from the platform users can offer their hardware components, books, slides, etc... to share it with others and sell it. And help them share bugs and problems they faced and get suggested solutions from other users. This platform makes it easy for computer engineering students to study and share knowledge with their collogues and access a resource in fast and easy way.